Taurine Alleviates Sympathetic Innervation by Inhibiting NLRP3 Inflammasome in Postinfarcted Rats. Issue 6 (June 2021) - Lee, Cheng-Che; Chen, Wei-Ting; Chen, Syue-yi; Lee, Tsung-Ming
Abstract : Abstract: The NLRP3 inflammasome is activated by myocardial infarction and then induces the activation of inflammatory caspase-1 activation and maturation of IL-1β, a regulator of synthesis of the nerve growth factor (NGF). Here, we studied whether taurine, 2-aminoethanesulphonic acid, can attenuate cardiac sympathetic reinnervation by modulating NLRP3 inflammasome-mediated NGF in a rat model of myocardial infarction. Male Wistar rats were subjected to coronary ligation and then randomized to either saline or taurine for 3 days or 4 weeks. Postinfarction was associated with activation of NF-κB (p65) and NLRP3 inflammasome component and increased the protein and expression of IL-1β. Macrophages at the border zone were shown to be positive for IL-1β 3 days postinfarction. Compared with vehicle, infarcted rats treated with taurine significantly attenuated myocardial messenger RNA and protein levels of NF-κB, NLRP3 inflammasome, mature caspase-1, and IL-1β. Immunofluorescent analysis, real-time quantitative reverse transcription polymerase chain reaction, and Western blotting of NGF showed that sympathetic hyperinnervation was blunted after administering taurine. Arrhythmia vulnerability in the taurine-treated infarcted rats was significantly improved than those in vehicle. Ex vivo studies showed that taurine infusion reduced myocardial IL-1β level at the extent similar to either pyrrolidine dithiocarbamate or CP-456, 773, inhibitors of NF-κB and NLRP3 inflammasome, implying the key axis of NF-κB/NLRP3 inflammasome in mediating taurine-related anti-inflammation. Furthermore, administration of anti-IL-1β antibody reduced NGF levels. Taurine attenuated sympathetic innervation mainly by NLRP3 inflammasome/IL-1β–dependent pathway, which downregulated expression of NGF in infarcted rats. These findings may provide a new insight into the anti-inflammation effect of taurine. Abstract : Supplemental Digital Content is Available in the Text.